2018
DOI: 10.3390/cancers10010021
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 Mediates the Oncogenic Effects of STAT3 in Anaplastic Large Cell Lymphomas

Abstract: Systemic anaplastic large cell lymphomas (ALCL) are a category of T-cell non-Hodgkin’s lymphomas which can be divided into anaplastic lymphoma kinase (ALK) positive and ALK negative subgroups, based on ALK gene rearrangements. Among several pathways aberrantly activated in ALCL, the constitutive activation of signal transducer and activator of transcription 3 (STAT3) is shared by all ALK positive ALCL and has been detected in a subgroup of ALK negative ALCL. To discover essential mediators of STAT3 oncogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…Recent studies have revealed interferon regulatory factor 4 ( IRF4 ) as a STAT3 key target gene, promoting survival of the neoplastic cells by activation of the transcription factor MYC. However, independently of IRF4 genetic alterations (translocations or overexpression), IRF4 has been shown to induce the survival of ALCL neoplastic cells [ 90 , 91 ]. In myeloma cells, this mechanism is described as an autoregulatory circuit, with IRF4 directly targeting MYC and at the same time IRF4 representing a direct target of MYC transactivation [ 92 ].…”
Section: Systemic Alk-positive Anaplastic Large Cell Lymphoma (Alkmentioning
confidence: 99%
“…Recent studies have revealed interferon regulatory factor 4 ( IRF4 ) as a STAT3 key target gene, promoting survival of the neoplastic cells by activation of the transcription factor MYC. However, independently of IRF4 genetic alterations (translocations or overexpression), IRF4 has been shown to induce the survival of ALCL neoplastic cells [ 90 , 91 ]. In myeloma cells, this mechanism is described as an autoregulatory circuit, with IRF4 directly targeting MYC and at the same time IRF4 representing a direct target of MYC transactivation [ 92 ].…”
Section: Systemic Alk-positive Anaplastic Large Cell Lymphoma (Alkmentioning
confidence: 99%
“…Anaplastic large-cell lymphoma, ALK+ [22,[24][25][26][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Anaplastic large-cell lymphoma, ALK− [22,25,46,52,56,[59][60][61] Breast Implant Associated anaplastic large-cell lymphoma [27,28,60] Angioimmunoblastic T cell lymphoma [22,46,62] Peripheral T cell lymphoma, NOS [22,46,63,64] T cell large granular Lymphocytic Leukemia [27,[30][31][32]46,65,66] NK/T cell lymphoma, nasal type and NK/T cell lymphoma [27,34,36,46,[67][68]…”
Section: Mature T and Nk Cell Neoplasms Relevant Literaturementioning
confidence: 99%
“…STAT3 also binds to and regulates the expression of interferon regulatory factor 4 (IRF4), a transcription factor important for promoting Th17 differentiation [21]. Chromatin immunoprecipitation revealed that STAT3 binds to the regulatory regions of IRF4 [58]. The STAT3 dependent expression of IRF4 appears to be involved in oncogenesis in ALK+ ALCL cells [58].…”
Section: Irf4mentioning
confidence: 99%
See 2 more Smart Citations